2021
DOI: 10.2147/idr.s277899
|View full text |Cite
|
Sign up to set email alerts
|

HIV and SARS-CoV-2 Co-Infection: What are the Risks?

Abstract: The dramatic increase of the global pandemic of SARS-CoV-2 infection represents a critical issue that needs to be investigated to evaluate the associated risk factors for acquisition and worse outcome. The interplay between immune activation and immune depression during SARS-CoV-2 infection is an intriguing topic that still needs to be clarified. The role of HIV in SARS-CoV-2 infection is not well defined. Chronic inflammation linked to HIV infection could be a driver for a worse prognosis in people living wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…When compared to influenza, there are many differences in terms of clinical features, morbidity and mortality ( 2 ), and more so when considering the CFR (case fatality rate) of COVID-19 [0.1-25%] ( 3 ) with that of the more recent pandemic of influenza A H1N1 of 2009 [0.001-0.011%] ( 4 ). Patients with cancer and transplant recipients have an increased risk of worse outcomes, but no evidence on worse prognosis has been demonstrated in patients with primary immunodeficiencies and human immunodeficiency virus (HIV) infection ( 5 , 6 ). However, patients with systemic autoimmune diseases and high doses of corticosteroids or rituximab seem to be associated with more unfavourable outcomes ( 7 ).…”
mentioning
confidence: 99%
“…When compared to influenza, there are many differences in terms of clinical features, morbidity and mortality ( 2 ), and more so when considering the CFR (case fatality rate) of COVID-19 [0.1-25%] ( 3 ) with that of the more recent pandemic of influenza A H1N1 of 2009 [0.001-0.011%] ( 4 ). Patients with cancer and transplant recipients have an increased risk of worse outcomes, but no evidence on worse prognosis has been demonstrated in patients with primary immunodeficiencies and human immunodeficiency virus (HIV) infection ( 5 , 6 ). However, patients with systemic autoimmune diseases and high doses of corticosteroids or rituximab seem to be associated with more unfavourable outcomes ( 7 ).…”
mentioning
confidence: 99%
“…For PLHIV, efforts such as vaccination minimize the chance of contracting COVID-19 disease, which might be one of the reasons for the relatively weak ability to produce antibodies and lower lymphocyte counts 47 . Treating co-infected individuals plays a vital role in reducing the number of deaths among HIV/AIDS patients.…”
Section: Resultsmentioning
confidence: 99%
“…HIV patients’ risk of transmitting the disease to another person or contracting another disease depends on their viral load. Following their compromised immunity, PLHIV may have an increased risk for severe disease from COVID-19 as well as hospitalizations 47 , 47 . This can be realized from Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the co-infection rate of COVID-19 among people living with HIV is similar to the general population. Similarly, most studies reported no increase in the incidence of COVID-19 among people living with HIV compared to the general population [34] , [35] . The co-infection rate of COVID-19 patients with obesity, CVDs, diabetes, chronic liver disease, CLD, malignancy and renal disease was 1.5%, 6.2%, 5.4%, 2.0%, 2.8%, 1.8% and 1.5% correspondingly.…”
Section: Discussionmentioning
confidence: 97%